1999
DOI: 10.1038/sj.leu.2401421
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a complex chromosomal translocation breakpoint t(10;14) including the HOX11 oncogene locus

Abstract: Based on cytogenetic studies, non-random chromosomal translocations which involve the HOX11 gene at locus 10q24 and the TCR genes at loci 7q35 or 14q11 have been reported to occur in 5% of T-ALL. HOX11, a member of the homeobox family of genes, has been shown to play a role in T-ALL. The activation of the HOX11 gene by translocations to the TCR locus results in the inappropriate expression of a 2.3 kb transcript. In this paper we describe a t(10;14)(q24;q11) breakpoint from a T-ALL patient specimen. The breakp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…The diminution in the incidence of SIL-TAL1 and HOX11L2 with age is in keeping with progressive diminution in the thymic ␣␤ lineage, but it does not explain the late onset of HOX11 T-ALL (Table 2). HOX11 is, at least partly, deregulated by the TCR␣/␦ or TCR␤ locus, 11,12,32,62 whose activity are also likely to diminish with age. An increasing number of "idiopathic" HOX11-expressing T-ALLs are recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The diminution in the incidence of SIL-TAL1 and HOX11L2 with age is in keeping with progressive diminution in the thymic ␣␤ lineage, but it does not explain the late onset of HOX11 T-ALL (Table 2). HOX11 is, at least partly, deregulated by the TCR␣/␦ or TCR␤ locus, 11,12,32,62 whose activity are also likely to diminish with age. An increasing number of "idiopathic" HOX11-expressing T-ALLs are recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Beta 1 integrin D U33880 ‫21.5מ‬ 0.0021 1.0000 1.0000 TPO up-regulates adhesion of hematopoetic progenitors to fibronectin through activation of integrin alpha4beta1 and alpha5beta1 (Gotoh et al 1997). Sp4 transcription factor X68561 ‫60.5מ‬ 0.0030 1.0000 1.0000 Sp4 not well characterized but closely related to Sp1 (Suske 1999), TPO activates several Sp1-dependent genes during megakaryopoiesis (Wang et al 1999 (Streit et al 1999), close relative thrombospondin 1 is negative regulator of megakaryopoiesis (Chen et al 1997;Touhami et al 1997 (Marlton et al 1995;Mancini et al 2000), CML/ALL translocations identified in 10q (Kagan et al 1989;Aguiar et al 1997;Salvati et al 1999 (Melnick et al 1999), isochromosomes on 17q common (Fioretos et al 1999) Biglycan J04599 ‫71.4מ‬ 0.2119 1.0000 1.0000 Xq28 Translocation found in AML (Weis et al 1985), common in ALL (Stern 1996 Dataset from Golub et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…HOX11 was first identified from the nonrandom chromosomal translocation t(10;14)(q24;q11) or variant t(7;10)(q35;q24), which occurs in up to 7% of T-cell acute lymphoblastic leukemia (T-ALL) cases (Kees et al, 1989;Dube et al, 1991;Hatano et al, 1991;Kennedy et al, 1991;Lu et al, 1991;Schneider et al, 2000). As a result of this translocation, HOX11 is placed under the transcriptional control of the TCR6 or TCRB regulatory elements (Lu et al, 1990;Kagan et al, 1994;Salvati et al, 1999). In the majority of cases, the protein product remains unaltered after translocation; hence, dysregulation of HOX11 is believed to be the key leukemogenic event (Kagan et al, 1989;Lu et al, 1990).…”
Section: Introductionmentioning
confidence: 99%